Ginx's Baby: His Birth and Other Misfortunes; a Satire - Jenkins, Edward, 1838-1910 (Salt Lake City, UT : Project Gutenberg, 1996)
"Ginx's Baby: His Birth and Other Misfortunes; a Satire" by Edward Jenkins is a satirical novel likely written in the late 19th century. The story begins with the birth of Ginx's Baby to Mrs. Ginx in a poor and overcrowded household, highlighting the struggles of working-class life in Victorian England. The narrative explores themes of poverty, societal neglect, and the conflicting responsibilities of parenthood through the lens of the Ginx family's experiences. The opening of the novel introduces us to Ginx, a navvy living in Westminster with his wife and their numerous children. The circumstances surrounding Ginx's thirteenth child reflect the dire conditions of their living situation, with hints of Ginx's frustration over his large family. Following the birth, Ginx contemplates extreme measures to alleviate their plight, leading to a dramatic confrontation with the community and authorities regarding his newborn. The narrative sets the stage for a critique of societal systems, including government and religion, as Ginx's Baby becomes the focal point for various groups eager to influence or control his future, showcasing a vivid snapshot of the complexities of 19th-century life and social issues. (This is an automatically generated summary.)
Release date is 1996-07-01
Produced by Charles Keller, and David Widger
Keywords: Orphans -- Fiction; Education -- Fiction; Satire, English; Christian sects -- Fiction